The Role of Implicit Associations and Ingroup Affiliation on Perceptions of Diversity - Fireside, Ethan; Gupta, Sangeeta (Journal of Advanced Research in Social Sciences, 2024)
Based on previous findings on subjective lengthening effects of unpleasant stimuli and overestimation of minority faces, the present study investigates how implicit associations and ingroup affiliation influence numerosity estimates of racially diverse faces. White and Black participants completed a numerical estimation task where they briefly viewed arrays with varying proportions of Black and White faces and determined which race appeared more numerous. Participants also completed the Implicit Association Test for race to assess implicit associations. Results showed that Black participants tended to overestimate outgroup faces and underestimate ingroup faces. Additionally, individuals with strong positive White associations overestimated the presence of White faces, but only in arrays featuring mostly White faces. These findings offer insights into the relative contributions of implicit associations and ingroup affiliation to perceptual biases.